2019
DOI: 10.1111/ics.12549
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age, gender and race/ethnicity on the composition of the human axillary microbiome

Abstract: Objective The microbial community plays an important role in the generation of human axillary odour by transforming odourless natural secretions into volatile odorous molecules. A limited number of traditional culturing methods and molecular based research have been performed to characterize the human axillary microbiome in small collection sample sizes. Moreover, only a few have considered the interpersonal variations across age, gender or race/ethnicity, and none have included all three variables within one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
3
22
1
Order By: Relevance
“…Skin bacterial diversity is driven by older infants. In line with previous work on the skin microbiome, samples from infants in both age groups in this study were dominated by Firmicutes, Actinobacteria, Proteobacteria, and Bacteroidetes (29,52,57,65,66,71,72). It is noteworthy that the differences in bacterial diversity across the skin sites are driven by individuals in the older age group (7 to 33 months) compared to the younger age group (0 to 6 months).…”
Section: Discussionsupporting
confidence: 90%
“…Skin bacterial diversity is driven by older infants. In line with previous work on the skin microbiome, samples from infants in both age groups in this study were dominated by Firmicutes, Actinobacteria, Proteobacteria, and Bacteroidetes (29,52,57,65,66,71,72). It is noteworthy that the differences in bacterial diversity across the skin sites are driven by individuals in the older age group (7 to 33 months) compared to the younger age group (0 to 6 months).…”
Section: Discussionsupporting
confidence: 90%
“…The production of malodor on the underarm skin is primarily attributed to the action of the resident microbiota on odorless natural secretions from the apocrine gland ( 24 ). Corynebacterium is one of the dominant bacterial groups in the armpit microbiota, which has an important role in malodor generation ( 25 ). Furthermore, a previous study revealed that the Anaerococcus species in sweat contributed to axillary odor ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…This microbial biotransformation of nutrients secreted in the human axilla undoubtedly leads to the development of odor characteristics and bacterial profiles that are observed. There is also the influence of genetic factors (gender and ethnicity) and behavioral patterns (diet) on the composition of human axillary odor, in addition to individual olfactory sensitivity for certain odorous compounds 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…The knowledge concerning axillary microflora and the differences between groups differentiated by gender, age, and ethnicity are fundamental today for the development of customized deodorant products. Li and colleagues 13 conducted a study on the influence of these characteristics on the axillary microbiome and report that there are significant differences between the species of Corynebacterium found in men and women, and this fact can be used to identify biomarkers for differentiating the microbiome between genders. There is also an increase in the diversity of Corynebacterium in older individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation